Sleep quality and cognitive impairments in remitted patients with schizophrenia in Nigeria. (2021)
Background. – Despite the ubiquity of sleep disturbance in schizophrenia, it has generally been overlooked as a potential contributor to cognitive impairments. The main aim of this study was to find out if impaired sleep quality contributes to cognitive impairments in patients with a diagnosis of schizophrenia who are in remission. Methods. – The study was conducted at the University College Hospital, Ibadan and State Hospital, Ibadan, Nigeria. The Pittsburgh Sleep Quality Index (PSQI) and Screen for Cognitive Impairment in Psychiatry (SCIP) were applied in this cross-sectional study, to all consecutive and consenting remitted outpatients with schizophrenia (N = 130). Other instruments such as Hamilton Depression Rating Scale (HDRS), the Positive and Negative Syndrome Scale (PANSS), sociodemographic and clinical measures were also applied. Results. – There were 130 participants made up of 69 females (53.1%) and 61 males(46.9%). The mean age of the participants was 38.5 ± 9.1 years. The prevalence of poor sleep quality in remitted patients with schizophrenia was 56.9%. Sleep quality was significantly negatively correlated with Verbal Learning Test-Immediate (VLT-I) (r(128) = -.18, P = .044) and Verbal Learning Test-Delayed (VLT-D) (r(128) = -.18, P = .037). The variables that independently predicted cognitive functioning were the VLT-I, odds ratio (OR) 0.66; 95% confidence interval ((CI) 0.49-0.88) and education (OR) 0.61;(CI) 0.40- 0.92). Conclusion. – Poor subjective sleep quality measured by the PSQI is linked to cognitive impairment in remitted patients with schizophrenia. We suggest that sleep quality in remitted patients with a diagnosis of schizophrenia should receive better attention by physicians.